Evidence-based practices to stimulate emergent literacy skills in kindergarten in France: A large-scale study. (August 2015) - Ecalle, Jean; Labat, Hélène; Le Cam, Marion; Rocher, Thierry; Cros, Laurent; Magnan, Annie
Abstract: In a randomized controlled trial with 3569 kindergarten children, evidence-based literacy practices (EBLP) were proposed by teachers to an experimental group (EG). A control group did not receive any specific interventions during the same period. The EBLP related to the alphabetic code, phonological awareness and oral comprehension. Analyses based on propensity scores showed significant gains in the targeted domains and in pseudoword reading in EG after comparison between the two groups. The gains were higher for children who had the lowest scores. However, no effect was observed in word reading and vocabulary. EBLP could be a valuable pedagogical tool. Highlights: Evidence-based (EB) literacy practices were proposed in a randomized controlled trial. Analyses involving propensity scores were conducted to examine their impact. These revealed a global effect on trained literacy skills in experimental group. The impact was more robust in the children with the lowest scores. The links between EB research, EB practices and EB policy are presented.